2014
DOI: 10.1021/am500254e
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Selective Adsorption of Lysozyme on Graphene Oxide

Abstract: Biosensing methods and devices using graphene oxide (GO) have recently been explored for detection and quantification of specific biomolecules from body fluid samples, such as saliva, milk, urine, and serum. For a practical diagnostics application, any sensing system must show an absence of nonselective detection of abundant proteins in the fluid matrix. Because lysozyme is an abundant protein in these body fluids (e.g., around 21.4 and 7 μg/mL of lysozyme is found in human milk and saliva from healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 51 publications
1
64
0
Order By: Relevance
“…18,25,[36][37] The results shown above demonstrated that the adsorbed proteins type varied according to the reduction degree and exposure concentration of GO/rGOs. It is relatively easy to understand the influence of reduction degree on adsorbed proteins type.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…18,25,[36][37] The results shown above demonstrated that the adsorbed proteins type varied according to the reduction degree and exposure concentration of GO/rGOs. It is relatively easy to understand the influence of reduction degree on adsorbed proteins type.…”
Section: Resultsmentioning
confidence: 79%
“…25 Undoubtedly, proteins adsorption will change the physicochemical properties of GO, like size and surface properties, and lead to loss of its functions. More seriously, this interaction may bring risks of capillary blockage resulted from the size increase.…”
Section: Introductionmentioning
confidence: 99%
“…The GO immobilized on the PDA film was spread out, and some folds and small wrinkles were observed clearly. This was caused by the carboxyl on the edge of the rGO and part of the hydroxyl on its basal plane can interact with amino group and part of hydroxyl on PDA mentioned in fount part . In addition, the large specific surface area structure on PDA/rGO film could provide more immobilized sites to cLY compared with pure PDA surface.…”
Section: Resultsmentioning
confidence: 99%
“…With recent nanotechnological developments in nanomedicine and biomedical engineering, much attention is focused on understanding the interaction and toxicity of nanomaterials on cellular components, such as proteins, plasma membranes and DNA [6][7][8][9][10]. Quantum dots (QDs), a class of typical nanoparticles, have been extensively studied with proteins to explore their potential biomedical applications.…”
Section: Introductionmentioning
confidence: 99%